Community Perceptions of Police Efforts in Law Enforcement (Study in the Resort Police Area, Pasaman District) - Prayitno, Rangga; Bimas Saputra, Ebit (Siber Journal of Advanced Multidisciplinary, 2023)
Purposeful research to find out the perception of the people of Pasaman Regency towards law enforcement by the Investigation Police at the Pasaman Regency Police . This study uses a qualitative approach. Research informants were selected based on purposive sampling technique . Types and sources of data used primary and secondary data, data collected through interviews and observation. The results of this study illustrate that the public's perception of the Police's efforts to enforce law in the Pasaman Regency area is currently not good, because the community still believes that the Police have not carried out their duties properly, judging from the law enforcement processes carried out by the Police, they are in accordance with their duties and functions. in accordance with the law.